Sosialisasi Neck Stretching Exercise Yang Benar Pada Ibu-Ibu di Sanggar Senam Prima Colomadu - Shella Dhika Rahmawati; Fitratun Najizah; Aulia Ayu Kusuma W (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Neck pain is a medical symptom or condition that is generally caused by pressure on the soft tissues, bones, or joints of the cervical spine and or other adjacent structures. In some cases, neck pain may also be caused by diseases of the neck or other underlying parts of the body. Risk factors for neck pain include poor posture, accidents, injuries and degenerative diseases may be the cause of neck pain in a person. Other causes such as infections in the lining (membranes) of the brain (meningitis), osteoarthritis, and fibromyalgia can be considered. Neck pain caused by muscle tension usually goes away on its own within a few days and only requires conservative treatment in the form of exercise, stretching, physical therapy, massage. Some forms of neck pain require professional medical care, including prescribing medications, physical therapy and other treatments. In severe cases, surgery may be necessary to manage neck pain. On May 19, 2022, we carried out Independent Community Service in Krobyongan Village, Gawanan, Colomadu District, Karanganyar Regency, Central Java (Sanggar Prima) with the theme of simple ways to overcome neck stiffness while working. Starting the counseling activity with neck pain material, how to overcome neck stiffness while working and exemplifying the movements, a question and answer session and ending by distributing snacks and questionnaires. The purpose of this activity is to increase knowledge on how to prevent neck pain and how to overcome neck stiffness while working at the prima colomadu studio. The method of implementing community service by: lectures, discussions, and providing simple tips and exercises.